Assessing Institutional Effectiveness of Medical Rehabilitation Programs for Drug Addicts by the National Narcotics Agency - Arsawati, Ni Nyoman Juwita; Antari, Putu Eva Ditayani; Anditya, Ariesta Wibisono (Nurani Hukum, 2024)
Narcotics abuse is a very complicated matter in Indonesia, even become alert and dangerous. The government's effort to deal with drug addicts is to provide medical rehabilitation and social rehabilitation. The purpose of this study was to find out and analyze related to the provision of rehabilitation for narcotics addicts at the Badung Regency National Narcotics Agency. The research method that the writer uses is the empirical legal research method through the fact approach and the statute approach. The primary data source that the writer uses is interviews, while secondary data is in the form of laws and regulations, journals, and books. The author's research location is the Badung Regency National Narcotics Agency. The implementation of rehabilitation by National Narcotics Agency is an ongoing rehabilitation that is divided into two stages, namely the rehabilitation and post-rehabilitation processes. The functions and benefits of rehabilitation for narcotics addicts are recovery, productivity, and social functioning. However, facilities, and infrastructure are still not effective because National Narcotics Agency in every regency has not a special place for inpatient care and detoxification tools to medical rehabilitation.